Business, ethics and law - McCarty, Richard (Journal of business ethics, 1988)
The comparative seriousness of business law and business ethics gives some business people the impression that there is nothing important in business ethics. The costly penalties of illegal conduct compared to the uncertain consequences of unethical conduct support a common illusion that business ethics is much less important than law for business people. To dispel the illusion I distinguish two perspectives from which we can view the relation of business and normative systems: the internal and external perspectives. I show that in one perspective, ethics is hardly less important than law, and in the other perspective it is more important, more fundamental than law. I conclude with a discussion of why business persons must place ethical and legal rules ahead of profits.